The Influence of Liquidity Ratios, Leverage, Profitability and Activity on Financial Distress of Infrastructure Companies in the Building Construction Subsector for the Period 2018 – 2022 - Ummayah, Siti Ruhanni; Hertina, Dede (GoAcademica Research & Publishing, 2024)
This research aims to determine the effect of liquidity, leverage, profitability and activity ratios on the financial distress of infrastructure companies in the building construction subsector listed on the Indonesia Stock Exchange in 2018 - 2022. The approach used is quantitative research. This research uses secondary data accessed through the official website of the Indonesia Stock Exchange with a population of 22 companies and a sample of 16 companies selected using the purposive sampling method and obtaining a sample of 80 observations. The data analysis technique uses panel data regression analysis with the Eviews9 test tool. The research results show that the Liquidity Ratio as proxied by the Current Ratio has a positive effect on financial distress, the Leverage Ratio as measured by the Debt to Asset Ratio (DAR) has a negative effect on financial distress, the Profitability Ratio as measured by Return on Assets (ROA) has a positive effect on financial distress, while the Activity Ratio which is proxied by Total Asset Turnover (TATO) does not affect financial distress. The calculation technique uses the Altman Z-Score method and financial ratio calculations. Therefore, researchers recommend utilizing this test model to predict financial distress because the accuracy that can be given is quite good so that companies can anticipate financial difficulties.